RANCANGAN MODEL PENGENTASAN KEMISKINAN MASYARAKAT PESERTA USAHATANI KONSERVASI LAHAN KERING DI ZONA TAMBANG EMAS PULAU LOMBOK - Candra Ayu (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2014)
ABSTRAK Tujuan penelitian adalah merancang model pengentasan kemiskinan petani pelaksana usahatani konservasi lahan kering yang eksistensinya terancam akibat alih fungsi lahan untuk aktivitas penambangan ilegal di zona tambang emas Pulau Lombok. Dasar pengembangan model adalah penciptaan nilai tambah agribisnis lahan kering agar berkelanjutan mendukung penghidupan masyarakat sekaligus melestarikan sumberdaya alam. Model sistem agribisnis terpadu dan berkelanjutan hasil penelitian, terdiri dari komponen: input/potensi pengembangan, kelompok sasaran, lokasi kegiatan, output/ luaran model, dampak positif/kekuatan serta tantangan pengembangan. Simulasi model berdampak positif terhadap perekonomian wilayah binaan, yakni memperbaiki kesejahteraan masyarakat, menumbuhkan agroindustri sejenis di luar binaan, menguatkan posisi jual petani, memotivasi petani non binaan untuk bertani/sebagai pemasok bahan baku, membuka peluang perdagangan bahan baku antar wilayah serta meredam minat menjadi penambang. ABSTRACT Objective of this research is to design poorness elevation model of farmer that is threatened it’s the agriculture system existence as result of switching function of farm for gold mine activity in illegal gold mine zone of Lombok Island. Development bases of model are creation of dry farming agribusiness added value that having sustainability supports subsistence of community living as well as preserves natural resources. Model of Sustainable Integrated Agribusiness System that resulted from the research, consists of six principal components, namely: input or its development potency, group of target, location of activity, output model, positive impact/strength and model development challenge. Simulation of the model affects economics of guidance region positively, namely improves community prosperity, grows the same agroindustrv outside of guidance region, strengthens farmer’s selling position, motivates non guidance farmer to improve their farming or as raw material supplier, opens commerce opportunity of raw material between regions and damps enthusiasm of farmer to become mineworker.